Life cycle of the tick Amblyomma humerale (Parasitiformes: Ixodida) in the laboratory. Issue 5 (3rd July 2020) - Martins, Thiago F.; Teixeira, Rodrigo H. F.; R. Benatti, Hector; Minervino, Antônio H. H.; Soares, Herbert S.; Soares, João F.; Labruna, Marcelo B.
ABSTRACT: The tick Amblyomma humerale is endemic to South America, where its adult stage has been reportedmostly from terrestrial tortoises, whereas larvae and nymphs have been reported on various species of reptiles, birds, and mammals. Herein, we evaluated for the first time the life cycle of A. humerale in the laboratory. For this purpose, larvae and nymphs were exposed to feed on six host species: Gallus gallus, Mesocricetus auratus, Calomys callosus, Chelonoidis carbonaria, Salvator meriana e, and Trachemys scripta . Adult ticks were exposed to feed on T. scripta . The life-cycle of A. humerale in the laboratory could be completed in an average period of ca. 200 days, considering prefeeding periods of 25 days for each of the parasitic stages. One bird species ( G. gallus ), one small mammal ( C. callosus ) and one reptile species ( C. carbonaria ) were the most suitable hosts for larvae; however, chickens ( G. gallus ) were the most suitable host for nymphs, whereas a turtle species ( T. scripta ) was highly suitable for adult ticks. These results corroborate field observations that indicated that the immature stages of A. humerale have a low host specificity, being able to feed successfully on reptiles, birds, and mammals, whereas reptiles are important hosts for the adult stage.